Bavarian cuisine - Boyko, Anna (My University, 2014)
The origins of Bavarian cuisine are rural. The cuisine typically includes many meat and Knodel dishes, and the prominent use of flour.
Keywords: регіональна кухня; regional cuisine; типова баварська регіональна страва; typical Bavarian regional dish; страви французького походження; french-influenced dishes; кнедлі; knödel; квашена капуста; sauerkraut; кафедра іноземних мов професійного спрямування